Partisipasi Masyarakat Dalam Program Terobosan Baru Kampung Madani Sebagai Upaya Mengurangi Angka Kemiskinan di Kota Surabaya - Lutfia Diva Rahmawati; Djoko Widodo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Poverty in Indonesia persists to this day, and it is the government's responsibility to at least reduce the poverty rate. Surabaya, as the second largest city after Jakarta with a population of 2,887,223 people, is poised to experience growth in the coming years. High levels of urbanization bring new challenges to Surabaya, such as urban-rural disparities with the existence of slum areas. The aim of this research is to deeply analyze the level of community involvement and contribution in implementing the New Breakthrough Program of Kampung Madani in Surabaya, as well as to identify the social, economic, cultural, and political factors that influence the level of community participation in the program. This research employs a qualitative approach, particularly in the form of descriptive research. The descriptive analysis aims to provide a clear, objective, systematic, analytical, and critical overview of community participation in the New Breakthrough Program of Kampung Madani as an effort to reduce poverty in Surabaya. The theory of community participation according to Yadaf (2012) is used in this research. The results of the research show that community participation in the New Breakthrough Program of Kampung Madani is quite significant, as evidenced by the enthusiasm of village officials and philanthropic individuals who willingly and sincerely help those in need.